Competitiveness of the Malaysian and Indonesian Palm Oil Exports - Cheng, Choon Huat (2001)
Indonesia's emergence in the palm oil trade could pose a strong threat to the current competitive advantage that Malaysia is enjoying as Indonesia has large land resources and an abundant supply of cheap labour. This study intends to evaluate the Malaysian and Indonesian palm oil exports performances in the last two decades and to identify the factors contributing to the competitiveness of the exports. The competitiveness of the Malaysian and Indonesian palm oil exports are measured using economic indicators like Revealed Comparative Advantage (RCA) and Constant Market Share (CMS) analysis; while the potential export markets are ascertained through Shift- Share technique. This study utilises annual data from 1987 to 1998. The twelve year period is decomposed into three sub periods with each period contains the four year average. Period I covers 1987-90, Period II covers 1991-94 and Period III covers 1995-98 for RCA and CMS analyses. The Shift-Share calculations involve only two time periods, that are Period I (1987-92) and Period IT (1993-98). The results of RCA clearly show that the Malaysian palm oil export still maintains strong comparative advantage. This is mainly due to the low level import of palm oil. However, Malaysia shows a declining trend in Export Performance Ratio throughout the periods of the study due to the declining share in world's palm oil export. In the case of Indonesia, the RCA calculations show an increasing strength of comparative advantage, which is attributed to the increasing palm oil export. CMS results suggest that export gains of palm oil for both countries are mainly attributed to the size of the market effect. Both countries show negative distribution effect, due to the concentration of exports to low growth importing countries. The eMS analysis also demonstrates that the competitiveness effect has contributed to the palm oil export growth of Indonesia. On the contrary, Malaysian competitiveness effect is negative between Periods I and II, Periods I and III, which is attributed to the reduction in the Malaysia's share in the world export market. The Shift-Share analysis suggests that the potential markets for palm oil export expansion for the two countries are almost similar, covering China, Pakistan and India. However, Malaysia has a better opportunity to increase her export to the EU countries. From the calculations, the study concludes that Indonesia shows a better competitiveness in the palm oil exports.